Reformulation of Secured Creditors' Execution Rights in Bankruptcy: Economic and Justice Perspectives - Luhut Sagala; Budi Santoso; Ery Agus Priyono (Faculty of Law, Mulawarman University, 2026)
The stability of the banking sector is crucial for economic development, yet resolving Non-Performing Loans (NPL) often faces severe legal hurdles during corporate bankruptcy. This article analyzes the normative conflict in Indonesia's legal framework, specifically between collateral laws that guarantee immediate execution rights (parate executie) and Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The objective of this study is to examine how Articles 56 and 59 of the Bankruptcy Law restrict the execution rights of secured creditors (separatist creditors) through a 90-day stay period and a strict two-month execution limit. This research uses a normative legal method with statute and case approaches, analyzed through the Economic Analysis of Law and John Rawls's Theory of Justice. The findings indicate that the current bankruptcy regime structurally limits the rights of secured creditors, often forcing the surrender of collateral to the receiver (kurator), where auction proceeds are significantly reduced by bankruptcy costs and receiver fees. This legal uncertainty slows down credit distribution and increases systemic financial risks. The article concludes that reformulating the bankruptcy legal framework is necessary to restore equitable execution rights for secured creditors, ensuring a balanced approach between corporate rescue mechanisms and creditor protection.